Modified Monkey Optimization Algorithm for Solving Optimal Reactive Power Dispatch Problem - Kanagasabai Lenin; B.Ravindhranath Reddy; M.Surya Kalavathi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2015)
In this paper, a novel approach Modified Monkey optimization (MMO) algorithm for solving optimal reactive power dispatch problem has been presented. MMO is a population based stochastic meta-heuristic algorithm and it is inspired by intelligent foraging behaviour of monkeys. This paper improves both local leader and global leader phases.  The proposed (MMO) algorithm has been tested in standard IEEE 30 bus test system and simulation results show the worthy performance of the proposed algorithm in reducing the real power loss.